Linear and non-linear relations between the high-frequency-limit conductivity, AC-ECM signals and ECM signals of Dome F Antarctic ice core from a laboratory experiment - Fujita, Shuji; Azuma, Nobuhiko; Motoyama, Hideaki; Kameda, Takao; Narita, Hideki; Matoba, Sumito; Igarashi, Makoto; Kohno, Mika; Fujii, Yoshiyuki; Watanabe, Okitsugu (International Glaciological Society, 2002)
journal article